The influence of an electromagnetic field on adipose-derived stem/stromal cells’ growth factor secretion: modulation of FGF-2 production by in vitro exposure - Trzyna, Anna; Pikuła, Barbara; Ludwin, Aleksandra; Kocan, Beata; Banaś-Ząbczyk, Agnieszka (Archives of Biological Sciences, 2020)
Paper description: Proteins secreted by adipose-derived stem/stromal cells have potential use in regenerative medicine. Exposure of adipose-derived stem/stromal cells to an electromagnetic field (EMF) (50 Hz; 1.5 mT) in vitro increased the concentrations of pro-regenerative proteins, mostly of basic fibroblast growth factor (FGF-2 protein). Exposure to an EMF improved the regenerative potential of adipose-derived stem/stromal cells. Cell exposure to an EMF can be used to obtain conditioned media with the cell secretome for regenerative medicine. Abstract: Adipose-derived stem/stromal cells (ASCs) have tremendous potential for use in regenerative medicine; their secretome is especially important for regenerative processes. We hypothesized that exposure of ASCs to an electromagnetic field (EMF) can influence the proregenerative potential of cells by influencing the secretion of growth factors (GFs) responsible for regenerative properties. We showed that the exposure of ASCs to an EMF (50 Hz; 1.5mT) affected the secretion of GFs as well as the cell cycle process. The most important observation was a statistically significant, 3-fold increase in FGF-2 concentration at 48 h, and a 2-fold decrease at 72 h when compared to the control group. This finding is very important for regenerative medicine, because with precisely adjusted parameters, an EMF can be used to stimulate the production of GFs, mainly of FGF-2, by ASCs, thereby increasing proregenerative properties. The ASC secretome after EMF treatment could be a method for easy, simple and cost-effective stem cell differentiation and therapy facilitation. https://doi.org/10.2298/ABS200321028T Received: March 21, 2020; Revised: May 18, 2020; Accepted: June 15, 2020; Published online: June 23, 2020 How to cite this article: Trzyna A, Pikuła B, Ludwin A, Kocan B, Banaś-Ząbczyk A. The influence of an electromagnetic field on adipose-derived stem/stromal cells’ growth factor secretion: modulation of FGF-2 production by in vitro exposure. Arch Biol Sci. 2020;72(3):339-47.